Practices of distributed leadership in two Islamic secondary schools - Amin, Syed Nazmul; Musah, Mohammed Borhandden; Tahir, Lokman Mohd; Farah, Adnan Mohammad; Al-Hudawi, Shafeeq Hussain Vazhathodi; Issah, Mohammad; Abdallah, Asma Khaleel (International Journal of Evaluation and Research in Education (IJERE), 2024)
Purpose-distributed leadership (DL) continues to draw practitioners and researchers’ attention in the context of education leadership as early as the 21st century. While an increasing amount of literature strongly advises principals to shift toward DL practices, there is a paucity of studies that indicate the extent to which this shift is taking place in practice across Islamic secondary schools. Consequently, this study investigates the distributed of leadership practices of two Islamic secondary schools located in two different countries. Design/methodology/approach-the study uses a collective case study methodology with a mixed-method approach, and collected data from 30 school teachers and interviews six school teachers. Findings-the findings reveal that both selected Islamic secondary schools have a definite hierarchy decided by top management. The findings also indicate that when leadership roles are distributed among classroom teachers, the schools do not seem to have fixed criteria. In addition, the findings illustrate that novice teachers are slowly given responsibilities and prepared to take on leadership roles. Implications–the findings could serve as a supportive literature in practicing DL across Islamic secondary schools to reduce the workload of headteachers. The findings further link DL to the development of a professional learning community though teacher leadership. Originality/value–The significance and originality of this research arguably falls along the fact that; it is the first of its kind to empirically investigate DL practices across Islamic secondary schools in two different geographical locations.